The uncanny valley: No need for any further judgments when an avatar looks eerie. (May 2019) - Shin, Mincheol; Kim, Se Jung; Biocca, Frank
Abstract: Considering that a 3D scanning technology allows to create avatars that embody more authentic and rich information about its users, it could be expected that enhancing avatar realism will increase the accuracy of thin-slice judgments of the person represented by the avatar. However, previous studies suggest that the objective realism of avatars may not always lead to positive outcomes, and the activation of negative affect and the aversive motivational system through the uncanny valley effects may rather harm the accuracy of thin-slice judgments by making people distance themselves from available information in avatars. To validate this speculation, a 2 (Realism: Cartoonish vs. Hyper-realistic) x 2 (Animacy: Still vs. Animate) between-subjects experiment (N = 134) was conducted. In support of our prediction, results from an online experiment confirmed that hyper-realistic and animate avatars can induce a greater feeling of eeriness as compared to cartoonish and still avatars. This feeling of eeriness, evoked by the uncanny valley effects, suppressed the amount of information processing oriented for thin-slice judgments, and subsequently decreased the accuracy of extraversion and agreeableness judgments. Further theoretical implications of the findings are discussed. Highlights: Avatar realism increased a feeling of eeriness. Eeriness predicts moderate to high level of the activation of aversive system. Eeriness inhibited the information processing oriented for thin-slice judgment (IP). The amount of IP determined the accuracy of extraversion judgments. The amount of IP also determined the accuracy of agreeable judgments.